Repeated-Sprint Performance, Locomotor Profile and Muscle Oxygen Uptake Recovery: Effect of Training Background - Ufland, P.; Ahmaidi, S.; Buchheit, M. (International Journal of Sports Medicine, 2013)
The aim of the present study was to examine the respective importance of locomotor profile and muscle oxygen uptake (mV˙  O2) recovery on repeated-sprint ability (RSA) and overall repeated-sprint performance. 11 sprint- (STR) and 10 middle-distance-trained (MDTR) athletes (20.8±4.0 yr) performed an incremental test and a 40-to-50-m sprint to estimate their maximal aerobic (MAS) and sprinting (MSS) speeds. They also performed 6×30-m sprints, departing every 30 s, where mean (RSmean) sprint time was calculated. Muscle oxygenation (Near-infrared spectroscopy, NIRS, [Hbdiff]) was measured for ~ 4 min post test. The mean response time of [Hbdiff]−mV˙  O2 recovery (monoexponential curve fitting, MRT[Hbdiff]−mV˙  O2) was calculated. Compared with MDTR, STR presented faster MSS (+11.4±6.7%, with 99% chances to observe a substantially greater value) and RSmean (−3.7±5.4%, 78%), but slower MAS (−15.8±8.0%, 100%) and MRT[Hbdiff]−mV˙  O2 (+46.2±31.7%, 96%). RSmean was largely correlated with MSS [r=−0.83 (90%CL, −0.92;−0.67)], but neither with MAS [r=−0.12 (−0.47;0.25)] nor MRT[Hbdiff]−mV˙  O2 [r=−0.27(−0.58;0.11)]. RSmean adjusted for MSS (which indirectly reflects RSA) was largely correlated with both MAS [r=0.51(0.18;0.74)] and MRT[Hbdiff]−mV˙  O2 [r=0.53(0.20;0.75)]. While a fast mV˙  O2 recovery is associated with an improved RSA, MSS remains of primary importance for overall repeated-sprint performance (i.e., RSmean).
Keywords: near-infrared spectroscopy; multiple sprint work; post-exercise recovery; endurance-training; sprint-training; maximal sprinting speed; maximal aerobic speed